Is Technology Mediated Learning Really Improving Performance Of Students? - Leonardo Caporarello; Massimo Magni; Ferdinando Pennarola (European Alliance for Innovation (EAI), 2016)
This paper examines the role of information technology in learning environments. In particular, it goes through the analysis of the impact of the use of information technology in high school students' performance. It describes and analyzes the initiative carried on by Impara Digitale Study Center: 370 students from different high schools experienced a full school year with a new teaching model, using tablets and computers instead of text books, according to a cooperative model, where each learner adopted his own device. The experience is paramount and it opens a stream of questions for further and more extensive diffusion, i.e. institutionalizing the adoption of personal devices in learning environments. We explored the different theories that can help with answers and we designed our research by using the widely adopted TAM Model, where grades are used as a measure of learning effectiveness. We also measured learning effectiveness in a control sample, using in the same schools same teachers and more traditional learning approaches. Our conclusions show that the new method improves students' performance only if teachers, who play a pivotal role in their technology acceptance, properly support them.